Terapi Kesehatan Mental Anak Remaja Perspektif Tasawuf - Irma Kodariah (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to determine mental health therapy for adolescents based on the perspective of Sufism. This study uses a qualitative approach using a descriptive-analytic method. The results and discussion in this study indicate that mental health is a state in which individuals can overcome the problems of life's pressures, work productively, realize their potential and be able to contribute to the surrounding environment. There is an urgency for mental health in adolescents because most people who experience mental disorders are in their teens. Where in this teenage period, the development phase has begun to move towards adulthood. Sufism on a broader scale, is a normative rule to create peace and tranquility, the unrest that is present in one's life can make tasawuf a positive compensation. Sufism is part of Islam which leads to self-approach to Allah SWT. Therefore Sufism in its value can be used as healing both physically and psychologically.